Past, Present, and Future of Insulin Pump Therapy: A Better Shot at Diabetes Control - Sherr, Jennifer (2008)
With the advent of continuous subcutaneous insulin infusion (CSII) therapy and the findings of the Diabetes Control and Complications Trial (DCCT) the management of type 1 diabetes has changed drastically. Over the past 30 years since its development, the effectiveness of CSII as compared to other modes of intensive treatment has been assessed. Additionally, improvements in pump delivery systems have been made. Herein the findings of the studies on pump therapy will be reviewed. Selection criteria of patients for pump use and how to initiate pump therapy will be presented. Finally, newer findings on continuous glucose sensors will be discussed as the next era of pump therapy continues to focus on the goal of developing an artificial pancreas.